A final size relation for epidemic models - Julien Arino; Fred Brauer; P. van den Driessche; James Watmough; Jianhong Wu (Mathematical Biosciences and Engineering)
A final size relation is derived for a general class of epidemic models, including models with multiple susceptible classes. The derivation depends onan explicit formula for the basic reproduction number of a general class of disease transmission models, which is extended to calculate the basic reproduction number in models with vertical transmission. Applications are given to specific models for influenza and SARS.